Coffee seedlings produced in tubes with different substrates in Sabanilla de Alajuela, Costa Rica - Chaves-Vargas, Hugo (2020)
A key factor in the production of seedlings is to guarantee a substrate that meets the requirements of texture, structure, fertility, and, above all, health to obtain healthy, vigorous plants with good development for the field stage. A practice to obtain seedbed at lower cost is the technique of seedbed in tubete. The objective of this study was to evaluate the growth and mortality of a coffee seedling produced by tubes on three different substrates. The trial was carried out in El Cerro, Sabanilla de Alajuela during the months of April to September 2015. Three substrates corresponding to the treatments were used, T1: commercial Peat Moss, T2: based substrate soil and compost coffee dregs and treatment, and T3: substrate prepared with soil mix, Ever Green super soil, and coconut fiber. No difference was determined in terms of substrates, so any of them can be used for the preparation of seedlings.  Regarding production costs, although there were differences between each substrate, each one was below the normal price of a seedling produced in the Central Valley. The growth variables analyzed (height, stem diameter, and leaf pairs) presented differences significant by means of the LSD Fisher statistical test (>0.05), for all the variables the behavior was T1 > T2 > T3. There were no losses in plants in any of the three treatments, so the percentage of mortality always remained zero. No difference was determined in terms of substrates, so any of them can be used to produce seedlings regarding both the materials used, as well as the cost of processing, which in all cases is less than the average cost of processing with other techniques. The decision of which substrate to use will depend on the criteria and the economic capacity of the producer.